2023
DOI: 10.1186/s12891-022-06044-8
|View full text |Cite
|
Sign up to set email alerts
|

Foot orthoses for flexible flatfeet in children and adults: a systematic review and meta-analysis of patient-reported outcomes

Abstract: Background This systematic review and meta-analysis examined the effectiveness of orthoses for flexible flatfeet in terms of patient-reported outcomes in children and adults. Methods EMBASE, Medline (OvidSP), Web-of-Science, Scopus, CINAHL, Cochrane Central Register of Controlled Clinical Trials, i.e., Cochrane Central and Pubmed were searched to identify relevant studies since their inception up to February 2021. We included randomized controlled … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…No article to date has provided evidence to justify the treatment of flexible, asymptomatic flatfeet; therefore, caution should be exercised when deciding to treat this condition. Plantar orthosis, sometimes combined with foot exercises, is debatable as an efficient mechanism to improve the plantar arch [38][39][40][41][42][43][44]; however, this can relieve medial arch pain associated with flatfoot [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No article to date has provided evidence to justify the treatment of flexible, asymptomatic flatfeet; therefore, caution should be exercised when deciding to treat this condition. Plantar orthosis, sometimes combined with foot exercises, is debatable as an efficient mechanism to improve the plantar arch [38][39][40][41][42][43][44]; however, this can relieve medial arch pain associated with flatfoot [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…A flowchart based on literature review and the authors' opinion summarizing the recommended management of pediatric flatfoot can be found in Figure 2 [12][13][14][15][16][17][18][19][24][25][26][38][39][40][41]44].…”
Section: Discussionmentioning
confidence: 99%
“…In a metaanalysis, Leonoor NT Oerlemans et al showed that due to the heterogeneity of study designs, it is not possible to conclude that foot orthoses are useful for the treatment of flexible flat feet in children and adults. However, after analyzing the data, it can be deduced that orthoses are useful in reducing pain in adults [16]. Minettchen Herchenröder et al performed a literature review to synthesize the evidence on foot orthoses in adults with flat feet.…”
Section: Discussionmentioning
confidence: 99%
“…10 Foot orthoses remain the most common form of management, despite the fact that their effectiveness is questionable. 5,11 This article's primary aim was to study pediatric flatfoot and its epidemiology in the Middle East and North Africa (MENA) region, to investigate the reasons that make parents seek medical attention, the prevalence of using foot orthoses, and if there was a reported improvement after using them.…”
Section: Introductionmentioning
confidence: 99%